2016
DOI: 10.1016/j.electacta.2016.10.098
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical signature of hen egg white lysozyme at the glycerol-modified liquid-liquid interface

Abstract: Electrochemical characterization of hen egg white lysozyme (HEWL) at a glycerolmodified interface between two immiscible electrolyte solutions (ITIES) was conducted using a microporous silicon membrane-supported gelled-1,6-dichlorohexane|water-glycerol interface. The electrochemical response of HEWL under these conditions is of interest for the system's potential application to the formation of isorefractive emulsified-ITIES, which offer practical opportunities for spectrophotometric analysis of interfacial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Therefore, the multivalent ion transfer behaviors by this approach have also been attempted to investigate. However, previous studies have shown that the transfer behaviors of multivalent biopolymers, such as some proteins, tend to follow an adsorption/transfer behavior at the L/L interface, which is significantly different from the behaviors of monovalent ions. This effect probably implied that the protein tended to form ion pairs with the anti-ions in the organic phase and adsorbed on one side of the interface.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, the multivalent ion transfer behaviors by this approach have also been attempted to investigate. However, previous studies have shown that the transfer behaviors of multivalent biopolymers, such as some proteins, tend to follow an adsorption/transfer behavior at the L/L interface, which is significantly different from the behaviors of monovalent ions. This effect probably implied that the protein tended to form ion pairs with the anti-ions in the organic phase and adsorbed on one side of the interface.…”
Section: Resultsmentioning
confidence: 97%